Light-trap Catch of the Common Cockchafer (Melolontha melolontha L.) Depending on the Atmospheric Ozone Concentration - NOWINSZKY, László (Acta Silvatica & Lignaria Hungarica, 2011)
The study deals the efficiency of light trapping of the Common Cockchafer (Melolonthamelolontha L.) (Coleoptera: Melolonthidae) in connection with the ozone concentration of air. Thedata of the Hungarian forestry light trap network were used for the years 1997 through 2006. Wecalculated relative catch values of from the number of caught insects. We assigned these to the ozonevalues of the respective days. For the classified date pairs regression equations were calculated. Weestablished that the light trapping is most effective if the ozone concentration is high. As opposed tothis, low ozone concentration reduces the success of the catch. Our results may be utilized in plantprotection and forest protection prognoses.